Corruption Policy Challenges in Combating Land Mafia: Experiences from Several Countries - Hartanto, Ponco; Suwadi , Pujiyono; Rustamaji , Muhammad; Kamil, Rizqan (Lembaga Contrarius Indonesia, 2024)
This study describes the criminal law technique used to eradicate land mafia in Indonesia, the UK, and the UAE, including corruption law. This is a normative comparative legal study. The results show that the first eradication of land mafia practices in Indonesia, the UK, and the UAE followed the same pattern. In the UK and UAE, law enforcement can use bribery offenses if land mafia practices involve public or state officials with bribery signs and money laundering offenses if the funds are manipulated. Second, no specific criminal law in Indonesia is used to eradicate land mafia practices. However, the law of corruption can be used if the practice causes state financial losses, bribery offenses can be used if the practice involves bribing state officials or public officials, and the Indonesian Criminal Code can be used if the practice involves stealing. Third, Technology can be used to prevent and reduce land mafia in Indonesia by ensuring transparency and accountability of maps and land ownership. The government's